Pengaruh E-Service Quality dan Brand Trust Terhadap E-Satisfaction Pada Aplikasi Maxim - Rumahorbo, Hiskia Fitri; Hidayat, Ahmad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This research aims to determine the effect of E-Service Quality and Brand Trust on E-Satisfaction in the Maxim application. This study uses a quantitative approach, specifically employing multiple linear regression analysis techniques. The data was evaluated using SPSS 29 software. The results of the study concluded that the E-Service Quality variable (X1) and the Brand Trust variable (X2) have a positive and significant effect on E-Satisfaction (Y) in the Maxim application. Based on the research results, it was found that the E-Service Quality and Brand Trust variables have a positive and significant impact on E-Satisfaction in the Maxim application. The calculated t-value for the E-Service Quality variable is 2.326 > the t-table value of 0.161 with a significance value of 0.000 < 0.05. Furthermore, the Brand Trust variable has a t-value of 3.767 > the t-table value of 0.161 with a significance value of 0.021 > 0.05. These results indicate that E-Service Quality and Brand Trust play important role in increasing E-Satisfaction in the Maxim application.